2022
DOI: 10.1101/2022.10.07.22280814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-pandemic cross-reactive humoral immunity to SARS-CoV-2 in Africa: systematic review and meta-analysis

Abstract: Background: Low numbers of recorded COVID-19 deaths in Africa may be due to undercounting and/or protection due to demographic and/or other factors, including pre-existing immunity. Several studies have assessed pre-pandemic samples for anti-SARS-CoV-2 antibodies with heterogeneous results. Methods: We performed a systematic review and meta-analysis of studies evaluating pre-pandemic African samples for anti-SARS-CoV-2 antibody activity using pre-set assay-specific thresholds for seropositivity. Data wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 70 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…33 Finally, a recent review of 26 publications confirmed a prominent SARS-CoV-2 seroreactivity in countries where malaria transmission occurs throughout and in datasets enriched in malaria cases, and reported associations of higher SARS-CoV-2 seroreactivity with Plasmodium parasitemia. 34 We have found that polyreactivity is higher in prepandemic African than European subjects, and positively correlates with anti-P.…”
Section: African Subjects Have Higher Rates Of Polyreactive Antibodie...mentioning
confidence: 69%
See 2 more Smart Citations
“…33 Finally, a recent review of 26 publications confirmed a prominent SARS-CoV-2 seroreactivity in countries where malaria transmission occurs throughout and in datasets enriched in malaria cases, and reported associations of higher SARS-CoV-2 seroreactivity with Plasmodium parasitemia. 34 We have found that polyreactivity is higher in prepandemic African than European subjects, and positively correlates with anti-P.…”
Section: African Subjects Have Higher Rates Of Polyreactive Antibodie...mentioning
confidence: 69%
“…A study with prepandemic samples from eight malaria endemic countries showed that malaria induces cross‐reactive antibodies against sialic acid on N‐linked glycans of the S protein 33 . Finally, a recent review of 26 publications confirmed a prominent SARS‐CoV‐2 seroreactivity in countries where malaria transmission occurs throughout and in datasets enriched in malaria cases, and reported associations of higher SARS‐CoV‐2 seroreactivity with Plasmodium parasitemia 34 …”
Section: Discusionmentioning
confidence: 98%
See 1 more Smart Citation
“…29 Several other studies have also reported the presence of cross-reactive antibodies in naïve or pre-COVID samples. [30][31][32][33] While several studies have assessed antibody variations in HCWs, few have investigated the association of sociodemographic factors. In a 10-month study of HCWs, IgG response was detected up to 10 months postvaccination.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified a total of 15 such SARS‐CoV‐2 spike protein epitopes that cross‐react with antibodies generated against various acute and chronic viral antigens 29 . Several other studies have also reported the presence of cross‐reactive antibodies in naïve or pre‐COVID samples 30–33 …”
Section: Discussionmentioning
confidence: 99%